2021
DOI: 10.3390/ijms22020722
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Elastase Deficiency Ameliorates Myocardial Injury Post Myocardial Infarction in Mice

Abstract: Neutrophils are recruited into the heart at an early stage following a myocardial infarction (MI). These secrete several proteases, one of them being neutrophil elastase (NE), which promotes inflammatory responses in several disease models. It has been shown that there is an increase in NE activity in patients with MI; however, the role of NE in MI remains unclear. Therefore, the present study aimed to investigate the role of NE in the pathogenesis of MI in mice. NE expression peaked on day 1 in the infarcted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The role of NE in patients with ARDS, including COVID-19, and sepsis have been reported in different studies [104][105][106][107]. Moreover, in an experimental mice model, Ogura et al reported that NE deficiency improves myocardial injury in post-myocardial infarction [108]. Based on previous reports, NE inhibition could potentially have positive effects on COVID-19 [109].…”
Section: Neutrophil Elastase Inhibitorsmentioning
confidence: 98%
“…The role of NE in patients with ARDS, including COVID-19, and sepsis have been reported in different studies [104][105][106][107]. Moreover, in an experimental mice model, Ogura et al reported that NE deficiency improves myocardial injury in post-myocardial infarction [108]. Based on previous reports, NE inhibition could potentially have positive effects on COVID-19 [109].…”
Section: Neutrophil Elastase Inhibitorsmentioning
confidence: 98%
“…The protective effect was associated with reducing neutrophil activation and vascular leakage [ 61 ]. NE reached its peak on day1 in the infarcted mouse hearts [ 62 ]. NE deficiency decreased mouse mortality, increased cardiac function, and reduced fibrosis in the non-infarcted myocardium [ 62 ].…”
Section: Neutrophil Elastase (Ne)mentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is characterized by higher catalytic activity of NE hydrolyzing extracellular matrix components (elastin, laminin, collagen, and fibronectin) which in turn release epidermal growth factor (EGF) and fibroblast growth factor (FGF), leading to adverse vascular remodeling ( Zhu et al, 1994 ; Taylor et al, 2018 ). NE-deficient mice possess an improved cardiac survival rate after myocardial infarction, indicating reduced inflammation and suppression of the Akt signaling pathway ( Ogura et al, 2021 ). Of interest is the fact that administration of Sivelestat, a NE inhibitor, restored cardiac functioning post myocardial infarction in mice ( Ogura et al, 2021 ).…”
Section: Neutrophil Serine Proteases In the Cardiovascular System In Health And Diseasementioning
confidence: 99%
“…NE-deficient mice possess an improved cardiac survival rate after myocardial infarction, indicating reduced inflammation and suppression of the Akt signaling pathway ( Ogura et al, 2021 ). Of interest is the fact that administration of Sivelestat, a NE inhibitor, restored cardiac functioning post myocardial infarction in mice ( Ogura et al, 2021 ). Moreover, elevated NE levels in plasma correlate with the severity of numerous cardiovascular diseases including coronary artery disease (CAD), ischemic heart disease, and angina pectoris ( Mehta et al, 1989 ; Bell et al, 1990 ; Smith et al, 2000 ).…”
Section: Neutrophil Serine Proteases In the Cardiovascular System In Health And Diseasementioning
confidence: 99%